International Financial Reporting Standard for Small and Medium-Sized Entities- a New Challenge for the European Union - Ana-Maria Pascu; Andreea Vasiliu (CES Working Papers, 2011)
In the context of the global economic crisis, small and medium enterprises are most affected. That is why the problem that arises more frequently is the harmonization of national legislation with the European legislation. The necessity to implement specific standards for SMEs appeared in order to provide them a beneficial framework for better economic and financial market positioning. In this respect, the International Accounting Standards Board issued in 2009 IFRS for SMEs, a referential aiming to the simplification of accounting procedures, reconciliation and increase of confidence of potential investors (stakeholders). The question of compatibility of these standards with the European Accounting Directives appears in situations where they may choose to use IFRS for SMEs. The aim of this paper is to evaluate the incompatibilities between IFRS for SMEs and the European Accounting Directives and to analyze the results concerning the implementation of the IFRS for SMEs in Europe. Through this article we want to contribute to the SME accounting area of knowledge.
Keywords: 330; IFRS for SMEs; compatibility; European Accounting Directives; harmonization; reconciliation; implementation